Influence of surfactants on the formation and growth of cadmium telluride nanoplatelets - A.S. Akhmetova; A.K. Ospanova; B.N. Yussupbekova; T.T. Alibay (Eurasian Journal of Physics and Functional Materials, 2023)
The article presents a comprehensive review of the current research on the use of surfactants in CdTe nanoplatelet synthesis, including a discussion of the various types of surfactants that have been used and their effects on nanoplatelet size, shape, and optical properties. Additionally, the article examines the mechanisms by which surfactants influence the growth and morphology of CdTe nanoplatelets, with a focus on the role of surfactant, size, and structure. Overall, this article provides a detailed analysis of the use of surfactants in the synthesis of CdTe nanoplatelets and highlights the potential for this approach to improve the performance of CdTe-based technologies. The dependences of the NPL absorption and photoluminescence spectra on acids used as surfactants are shown. The dependence of the shape and size of the NPL on the length of the surfactant ligand was found.